Návrh strategie rozvoje malého rodinného vinařství na Moravě - Balga, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce se zaměřuje na představení návrhu strategického rozvoje malého rodinného vinařství Stávek, sídlícího na Jižní Moravě. V teoretické části jsou vymezeny základní pojmy pro lepší pochopení problematiky rozvoje a růstu společnosti. V analytické části následně je zhodnocen současný stav podniku pomocí vybraných analytických metod. Toto zhodnocení bude sloužit jako podklad pro rozhodování o určení dalšího směru rozvoje. V návrhové části je podrobněji rozepsána vhodná strategie rozvoje včetně harmonogramu změn.

The diploma thesis is focused on the proposal of strategic development of the small family winery Stavek located in South Moravia. The theoretical part defines the fundamentals necessary for better understanding the issues of the development and growth of the company. The current situation of the company is evaluated in the analytical part by using selected analytical methods. This evaluation will serve as a basis for deciding on the next strategic directions. The most suitable development strategy is specified in the design part of this thesis and includes schedule of changes for the near future.
The Proposal of Small Business Development Strategy for a Family Winery in Moravia Region
Keywords: rozvoj podniku; rodinný podnik; vinařství; marketing; strategie; business development; family business; winery; marketing; strategy